The Effect Of Business Strategy, Digital Transformation, And Competitive Advantage On Firm Performance - Mayndarto, Eko Cahyo; Arijanti, Susi; Susilowati, Eko Meiningsih; Sampe, Ferdiandus (Journal Management & Economics Review (JUMPER), 2025)
This study investigates the effects of business strategy, digital transformation, and competitive advantage on firm performance among medium and large enterprises operating in Indonesia across various sectors. Using a purposive sample of 200 firms, data were collected from top- and mid-level managers and analyzed through multiple linear regression and mediation analysis. The results indicate that business strategy and digital transformation both have significant positive impacts on firm performance, with competitive advantage serving as the strongest predictor. Moreover, competitive advantage partially mediates the relationship between business strategy, digital transformation, and firm performance, highlighting its critical role in translating strategic and technological efforts into superior outcomes. These findings contribute to strategic management literature by integrating traditional and digital perspectives, offering practical insights for managers aiming to improve organizational performance in the context of rapid technological change and market competition. Limitations and directions for future research are also discussed.